2009
DOI: 10.1007/s00467-009-1166-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of all-trans retinoic acid on renal expressions of matrix metalloproteinase-2, matrix metalloproteinase-9 and tissue inhibitor of metalloproteinase-1 in rats with glomerulosclerosis

Abstract: In kidney injury the accumulation of extracellular matrix (ECM) plays an important role and precedes the development of glomerulosclerosis (GS). There is great interest in agents that may interfere with such accumulation of ECM. Therefore, a rat model of GS was established to investigate the effect of all-trans retinoic acid (ATRA) on the renal expressions of matrix metalloproteinase-2 (MMP-2), matrix metalloproteinase-9 (MMP-9) and tissue inhibitor of metalloproteinase-1 (TIMP-1). Eighty Wistar rats were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
(31 reference statements)
1
17
0
Order By: Relevance
“…The sequences of oligonucleotides and sizes of PCR products were, for CNP, sense: 5'-AACATCCCAGACCGCTCATG-3', antisense: 5'-CAA GAA GGG CTT GTC CAA AGG-3'(73 bp) 9 for NPR-B, sense: 5'-AAC GGG CGC ATT GTG TAT ATC TGC GGC-3', antisense: 5'-TTA TCA CAG GAT GGG TCG TCC AAG TCA-3' (692 bp) 10 for NPR-C, sense: 5'-ATA GTG CGC TAC ATC CAG GGC AGT-3', antisense: 5'-TCC AAA GTA ATC ACC AAT GAC CTC CTG GGT ACC TGC-3' (573 bp) 10 for NEP, sense: 5'-CCC CGC CGG CAT TT-3', antisense: 5'-GCC CCC ATA GTT CAA TGA GTT G-3' (66 bp) 11 for glyceraldehyde-3-phosphate dehydrogenase (GAPDH), sense: 5'-TGT GAG GGA GAT GCT CAG TG-3', antisense: 5'-GGC ATT GCT CTC AAT GAC AA-3' (229 bp). 12 One microgram total RNA from the renal tissue of each rat was reverse transcribed into cDNA with an ExScript RT reagent kit (Takara Biotechnology Co. Ltd, Dalian, China). CNP, NPR-B, NPR-C and NEP were amplified with SYBR Premix Ex Taq (Takara Biotechnology Co. Ltd).…”
Section: Real-time Pcrmentioning
confidence: 99%
“…The sequences of oligonucleotides and sizes of PCR products were, for CNP, sense: 5'-AACATCCCAGACCGCTCATG-3', antisense: 5'-CAA GAA GGG CTT GTC CAA AGG-3'(73 bp) 9 for NPR-B, sense: 5'-AAC GGG CGC ATT GTG TAT ATC TGC GGC-3', antisense: 5'-TTA TCA CAG GAT GGG TCG TCC AAG TCA-3' (692 bp) 10 for NPR-C, sense: 5'-ATA GTG CGC TAC ATC CAG GGC AGT-3', antisense: 5'-TCC AAA GTA ATC ACC AAT GAC CTC CTG GGT ACC TGC-3' (573 bp) 10 for NEP, sense: 5'-CCC CGC CGG CAT TT-3', antisense: 5'-GCC CCC ATA GTT CAA TGA GTT G-3' (66 bp) 11 for glyceraldehyde-3-phosphate dehydrogenase (GAPDH), sense: 5'-TGT GAG GGA GAT GCT CAG TG-3', antisense: 5'-GGC ATT GCT CTC AAT GAC AA-3' (229 bp). 12 One microgram total RNA from the renal tissue of each rat was reverse transcribed into cDNA with an ExScript RT reagent kit (Takara Biotechnology Co. Ltd, Dalian, China). CNP, NPR-B, NPR-C and NEP were amplified with SYBR Premix Ex Taq (Takara Biotechnology Co. Ltd).…”
Section: Real-time Pcrmentioning
confidence: 99%
“…In our previous study, we found that ATRA could achieve a similar effect to a RAAS inhibitor (benazepril) to prevent the progression of GS lesions in GS rats. 9,10 However, whether the ATRA treatment was associated with the expression of RAAS in GS rats was not elucidated. This study was performed to investigate the association of ATRA treatment with RAAS expression.…”
Section: Introductionmentioning
confidence: 99%
“…Wagrowska- Danilewicz et al [8] found that the expression of both MMP-2 and TIMP-1 were upregulated in reanal allografts of 17 chronic allograft nephropathy patients compared to renal tissue of 11 normal controls, which suggest the remodeling of impaired renal structure have correlation with the regulation imbalance of MMP-2 and TIMP-1. The expression of TIMP-1 was downregulated, while the mRNA and protein expression and activities of MMP-2 and MMP-9 were enhanced after treatment with benazapril and all-trans retinoic acid (ATRA) in Wistar rat model of glomerular sclerosis compared to normal group [9]. The results of above studies suggest the ATRA exerts protection role by downregulate the expression of TIMP-1 and upregulate the mRNA expression and activity of MMP-2 and MMP-9, regulate the balance of the ratio of MMPs and TIMPs, and thus decrease ECM sediment.…”
Section: Discussionmentioning
confidence: 99%